Measuring the effect of monetary shocks on European sovereign country risk: An application of GVAR models - Asena Temizsoy; Gabriel Montes-Rojas (Journal of Applied Economics, 2019)
This paper investigates the effect of European monetary policies on Eurozone countries' sovereign risks. We control for interdependencies across individual variables within and across countries using a global VAR specification weighting transmission by their fiscal position. We find evidence of positive correlation between sovereign bond CDS and risk aversion for almost all countries in the Eurozone. The effects are larger after the 2012 Greek debt crisis. When the ECB increases its refinancing rate or there is a decline in money aggregates (i.e., M3), we observe an increase in sovereign bonds' risk of all countries (except Greece). In contrast, monetary policy tightening shocks have the opposite impact on Greece due to a differentiation effect.
Keywords: 330; CDS; Global VAR; sovereign risk in the Eurozone